2000
DOI: 10.1021/ja991357+
|View full text |Cite
|
Sign up to set email alerts
|

Orientation and Motion of Interlamellar Water:  An Infrared and NMR Investigation of Water in the Galleries of Layered Cd0.75PS3K0.5(H2O)y

Abstract: The motion of water in the galleries of layered Cd0.75PS3K0.5(H2O)1.2, prepared by the ion-exchange intercalation of hydrated potassium ions into CdPS3, have been investigated using a combination of orientation dependent NMR and infrared (IR) spectroscopies as a function of temperature. Within the galleries of the intercalated compound the potassium ions are displaced toward the layers and are immobile, while the water molecules form monolayer-thick two-dimensional islands. Two types of interlamellar water are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 28 publications
0
23
0
1
Order By: Relevance
“…5 Complete ion-exchange intercalation was ascertained by the absence of the host 00l reflections and the appearance of new 00l reflections with lattice spacing, 9.4 Å. 4 The intercalation of PEO in Cd 0.75 PS 3 Li 0.5 (H 2 O) 2 was carried out by refluxing the lithium-ion-exchanged intercalation compound Cd 0.75 PS 3 Li 0.5 (H 2 O) 2 with a methanolic solution of PEO ͓molecular weight (M w )ϭ6ϫ10 5 ] following the procedure reported in Ref. 5:…”
Section: A Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Complete ion-exchange intercalation was ascertained by the absence of the host 00l reflections and the appearance of new 00l reflections with lattice spacing, 9.4 Å. 4 The intercalation of PEO in Cd 0.75 PS 3 Li 0.5 (H 2 O) 2 was carried out by refluxing the lithium-ion-exchanged intercalation compound Cd 0.75 PS 3 Li 0.5 (H 2 O) 2 with a methanolic solution of PEO ͓molecular weight (M w )ϭ6ϫ10 5 ] following the procedure reported in Ref. 5:…”
Section: A Preparationmentioning
confidence: 99%
“…These compounds also serve as model systems for understanding the effect of confinement on properties of the guest in relation to those in the bulk. 3,4 Here we focus on a polymer electrolyte, Lipolyethylene-oxide ͑Li-PEO͒, confined by intercalation within the galleries of an inorganic layered host CdPS 3 . 5 The Li-PEO CdPS 3 -based intercalated polymer electrolyte Cd 0.75 PS 3 Li 0.5 (PEO) has been characterized previously 5 and a detailed study of the conductivity and dielectric properties reported.…”
Section: Introductionmentioning
confidence: 99%
“…Die Lage und Aufspaltung der Pake‐Dublettsignale änderte sich nicht mit der Temperatur, und der Austausch zwischen den frei beweglichen und fest gebundenen Molekülen war mindestens 10 6 ‐mal langsamer als im Volumenwasser. Die starre Umgebung der Wassermonoschichten verhinderte offensichtlich die Erweiterung der Hydrathülle und verlangsamte damit Austauschreaktionen 116…”
Section: Unbewegliche Wassergelöste Moleküle An Grenzflächenunclassified
“…These compounds also serve as model systems for understanding the effect of confinement of the guest on properties in relation to those in bulk [13,14]. Among the most commonly used inorganic layered host, montmorillonite is a favored choice in view of its special features of high aspect ratio (∼1000), high cationexchange capacity (CEC ∼80 meq/100 g), large specific surface area (∼31.82 m 2 g −1 ), appropriate interlayer charge (∼0.55) and length scale (clay channel width = 16 Å).…”
Section: Introductionmentioning
confidence: 99%